A comparison of structure, bonding and non-covalent interactions of aryl halide and diarylhalonium halogen-bond donors - Javaly, Nicole; McCormick, Theresa M.; Stuart, David R. (Beilstein Journal of Organic Chemistry, 2024)
Halogen bonding permeates many areas of chemistry. A wide range of halogen-bond donors including neutral, cationic, monovalent, and hypervalent have been developed and studied. In this work we used density functional theory (DFT), natural bond orbital (NBO) theory, and quantum theory of atoms in molecules (QTAIM) to analyze aryl halogen-bond donors that are neutral, cationic, monovalent and hypervalent and in each series we include the halogens Cl, Br, I, and At. Within this diverse set of halogen-bond donors, we have found trends that relate halogen bond length with the van der Waals radii of the halogen and the non-covalent or partial covalency of the halogen bond. We have also developed a model to calculate ΔG of halogen-bond formation by the linear combination of the % p-orbital character on the halogen and energy of the σ-hole on the halogen-bond donor.
Keywords: aryl halide; diarylhalonium; halogen; halogen bond; non-covalent interaction